Toward Self-Authoring a Civic Teacher Identity: Service-Learning in Teacher Education - McLean, Lorna; Truong-White, Hoa (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2016)
Previous scholarship has examined how teachers’ civic knowledge and conceptions of citizenship influence their goals, pedagogical practices, and confidence in teaching citizenship, but few studies have probed how teacher candidates develop identities as civic educators through community service-learning projects. This case study draws upon Baxter Magolda’s framework of self-authorship to investigate how teacher candidates in a Canadian university began to self-author their identities as civic educators through their experience of developing and delivering citizenship learning modules to youth through a community-based project. Our qualitative analysis of the data indicates that participating in change-oriented service-learning can lead teacher candidates to challenge their assumptions about youth engagement, increase their sense of self-efficacy as civic educators, and, to some extent, develop an awareness of self in relation to others.